Evaluation of aquifer protective capacity and soil corrosivity in Okerenkoko, Warri-Southwest, Delta State, using one-dimensional resistivity inversion - Okiotor Michael Edirin; Ezeh stanley; Owonaro Bodisere Jennifer; Saleh A. Saleh; Eriunu O. Meshack (International Journal of Research and Innovation in Applied Science (IJRIAS) |, 2022)
Thirty (30) Vertical electric soundings (VES) were acquired in Okerenkoko community Warri-Southwest, Delta State, to evaluate the protective capacity and soil corrosivity of the area which falls within the oil producing communities in the Niger Delta. Evaluation of longitudinal conductance of the area showed areas with poor (< 0.1 mho), weak (0.1-0.19 mho), good (0.7-4.9 mho), very good (5-10.0 mho) and excellent (> 10.0 mho) protective capacities. The study has shown that the protective capacity of most parts of the community were rated excellent, very good and good, hence aquifers in these areas are protected from contamination by oil spillage in the event of pollution, while areas with weak and poor protection capacity are susceptible to groundwater contamination from surface spills and other near surface phenomena. Soil corrosivity evaluation from VES data indicated the presence of slightly corrosive, moderately corrosive and practically noncorrosive materials in the subsurface. The areas with slight and moderate corrosivity are prone to pipeline failure. Therefore, environmental management programs should be considered in the area for the protection of the aquifer system in the community. This study serves as a useful guide for location of subsurface aquifers and their protection capacity distributions throughout the study area. This will assist in planning of exploration programs for sitting of groundwater production wells in the area.
Keywords: Aquifer protection; longitudinal unit conductance; Corrosivity; Vertical electrical sounding (VES); Resistivity inversion.